Constant light blocks diurnal but not pulsatile release of luteinizing hormone in the ovariectomized rat. - Watts, A; Fink, G (1981)
We have investigated the effects of constant light on the patterns of LH release in long-term ovariectomized rats. Some animals were implanted with a silicone elastomer capsule containing oestradiol-17 beta. Plasma samples in anaesthetized animals were taken from the external jugular vein and in conscious animals from an indwelling intra-atrial catheter. The pulsatile release of LH that occurred in animals not treated with oestrogen was unaffected by constant light or the steroid anaesthetic alphaxalone plus alphadolone acetate (Althesin), but was abolished by sodium pentobarbitone. However, the diurnal release of LH produced by increasing the concentrations of plasma oestradiol in conscious animals was blocked by constant light. Thus, these two rhythms of LH release are controlled by different neural pathways; the one concerned with diurnal LH release being suppressed by exposure to constant light.